PENGARUH INVESTMENT OPPORTUNITY, INTERNAL CASH FLOW, INSIDER OWNERSHIP, FIRM SIZE, Dan GROWTH SALES TERHADAP CAPITAL EXPENDITURE (Students' Journal of Accounting and Banking, 2015)
The purpose of this study was to analyze the influence of investment opportunity, internal cash flow, insider ownership, firm size and growth sales of the capital expenditure. The populationsof this study is manufacturing companies which are listed in Indonesia Stock Exchanged during 2009-2013. The purposive sampling was used in this study. The writer has selected 21 manufacturing companies as sample in this study. The writer used multiple linear regression analyse and using t-test to analyse, the significant level of the test convering normality test, multicollibearity, heteroscedasticity test and autocorrealation test. The result of the study can be concluted that the Investment opportunity and  firm size of the company have a positive effect on capital expenditure. While Internal cash flow, insider ownership and growth sales has no effect on capital expenditure. For furtner research, writer is recommended to examine all companies listed on the indonesian stock exchange, not only manufacturing compaies alone but to all companies.Keywords: Capital Expenditure, Investment Opportunity, Internal Cash Flow, Insider Ownership, Firm Size, and Growth Sales